2006
DOI: 10.1590/s0102-311x2006000400021
|View full text |Cite
|
Sign up to set email alerts
|

AIDS incidence and mortality in injecting drug users: the AjUDE-Brasil II Project

Abstract: This paper presents AIDS incidence and mortality among injecting drug users (IDUs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…The main risk factors for HCV infection in this group appear to be related to the characteristics of initiation into drug injecting, including age at initiation, duration and frequency, type of drug injected, and sharing of injecting equipment, expressed here as "giving or receiving syringes and needles", aspects discussed in the work by Zocrato et al 10 . Sexual transmission of HCV, although controversial, has been documented by growing evidence in male populations, especially those living with HIV/AIDS and who report unprotected sex with other men 9,11,17 . Suffice it to recall that some 30% of our sample reported a history of sex with other men, and that Ferreira et al 11 may not have identified such an association due to this infection's high prevalence in their study population and the undeniably preponderant role of parenteral transmission in this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main risk factors for HCV infection in this group appear to be related to the characteristics of initiation into drug injecting, including age at initiation, duration and frequency, type of drug injected, and sharing of injecting equipment, expressed here as "giving or receiving syringes and needles", aspects discussed in the work by Zocrato et al 10 . Sexual transmission of HCV, although controversial, has been documented by growing evidence in male populations, especially those living with HIV/AIDS and who report unprotected sex with other men 9,11,17 . Suffice it to recall that some 30% of our sample reported a history of sex with other men, and that Ferreira et al 11 may not have identified such an association due to this infection's high prevalence in their study population and the undeniably preponderant role of parenteral transmission in this population.…”
Section: Discussionmentioning
confidence: 99%
“…The IDUs population using SEP services also displays a profile of high vulnerability and social marginalization, as represented by a large portion of subjects experiencing difficulties with employment and housing, in addition to a high proportion of lifetime incarceration 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary analyses, which were subsequently performed, showed that the process of AIDS becoming more associated with poverty, women, heterosexuals and the Brazilian countryside occurred concomitantly with the following: the maintenance of high rates of prevalence in specifi c populations, notably homosexuals, injecting drug users (IDU), sex professionals and incarcerated populations; 2,8,12,18,25,a the regional and social differences in Brazil, which caused different types of behavior of the disease, with the reduction in the number of cases in the Southeastern and CentralWestern regions and increase in the Northern and Northeastern regions; and the increase in the number of cases among individuals aged more than 60 years and young homosexuals. 5,10,24 In addition, intimately associated with the fact that the Southeastern region, particularly the state of São Paulo, has the greatest and oldest epidemics, epidemiological analyses began to show a stabilization in the general AIDS incidence and HIV prevalence rates in Brazil, in the 2000s.…”
Section: Aidsmentioning
confidence: 99%
“…Eight cross-sectional [37][38][39][40][41][42][43][44] and eight ecologic studies [45][46][47][48][49][50][51][52] were excluded from the analysis because they examined absolute and relative differences in mortality risk for HIV/AIDS according to the socioeconomic characteristics of the area of patients' residence at the time of AIDS diagnosis. Therefore, it was not possible to determine the extent of mortality due to poor survival of people with HIV/AIDS versus differences in HIV incidence and prevalence by socioeconomic group.…”
Section: Literature Searchmentioning
confidence: 99%